2008
DOI: 10.1177/000313480807401115
|View full text |Cite
|
Sign up to set email alerts
|

Value of Ultrasound Guidance in Placement of Hemodialysis Access Catheters in Patients with End-Stage Renal Disease

Abstract: The increasingly frequent use of ultrasound for the placement of central venous catheters has shown improved results. This study examined the role of ultrasound in the placement of hemodialysis access catheters in patients with end-stage renal disease. The subjects were all end-stage renal disease patients admitted to our hospital between January 2004 and April 2005 and who underwent ultrasound-guided placement of a hemodialysis catheter in a central vein. All patients underwent perioperative ultrasound assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In a study of patients that had undergone CVC insertion 9‐19 weeks earlier, 50% of patients had an IJV thrombosis or stenosis leading to selection of an alternative site. In this study, use of ultrasound for a preprocedural site evaluation reduced unnecessary attempts at catheterizing an occluded vein 41 . At least two other studies demonstrated an appreciable likelihood of thrombosis.…”
Section: Recommendationsmentioning
confidence: 66%
See 1 more Smart Citation
“…In a study of patients that had undergone CVC insertion 9‐19 weeks earlier, 50% of patients had an IJV thrombosis or stenosis leading to selection of an alternative site. In this study, use of ultrasound for a preprocedural site evaluation reduced unnecessary attempts at catheterizing an occluded vein 41 . At least two other studies demonstrated an appreciable likelihood of thrombosis.…”
Section: Recommendationsmentioning
confidence: 66%
“…In this study, use of ultrasound for a preprocedural site evaluation reduced unnecessary attempts at catheterizing an occluded vein. 41 At least two other studies demonstrated an appreciable likelihood of thrombosis. In a study of bariatric patients, 8% of patients had asymptomatic thrombosis 38 and in another study, 9% of patients being evaluated for hemodialysis catheter placement had asymptomatic IJV thrombosis.…”
Section: We Recommend That Providers Should Use Two-dimensional Ultra...mentioning
confidence: 98%
“…The preferred site of catheter insertion is the right internal jugular vein. The catheter should be inserted with the use of ultrasonographic guidance [27][28][29] and with adherence to infection-control policies. 30 The use of tunneled catheters is warranted in patients who require prolonged renal-replacement therapy (>1 to 3 weeks) and is associated with a lower rate of infection and thrombosis than the rate associated with nontunneled catheters.…”
Section: Clinic a L Usementioning
confidence: 99%
“…In those patients, vascular accesses are long-lasting, so an arteriovenous fistula (AVF) is the most appropriate technique. When an AVF is not technically feasible or when patients require dialysis during the maturation of the AVF, a hemodialysis catheter in the central veins represents the most widely used option [ 29 , 80 , 81 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%